2020
DOI: 10.31695/ijasre.2020.33604
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Technology, Demography, and Financial Literacy on Financial Management Behavior of Productive Age in Surabaya, Indonesia

Abstract: This study aims to examine the effect of financial technology, demographics, and financial literacy on the financial decision making of the productive age population in Surabaya. The type of research is quantitative and conclusive in the form of causality. The data used are primary data obtained from the questionnaire. The population which is used as much as 180 respondents was selected by way of judgmental sampling. The characteristics of respondents are the productive age population in Surabaya who has incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 9 publications
9
32
0
2
Order By: Relevance
“…Based on the results of data analysis using SmartPLS, it obtained p value 0.000 < 0.050 so it can be concluded that Financial Literature had a significant effect on Students' Personal Financial Management, an increase in the Literature on Students variable would have a significant effect on an increase in the Students Personal Financial Management variable and a decrease in the Financial Literature variable would have an significant effect to the decrease in the Student Personal Financial Management variable. These results are in line with the research conducted by Chuah et al (2020), Cherney et al (2020), Humaidi et al (2020) that Financial Literature had a positive and significant effect on Students' Personal Financial Management. It concludes that personal management can be influenced simultaneously by variables of financial literacy, socioeconomic status, and lifestyle.…”
Section: Relationship Of Parents Social Economic On Students Personal Financial Managementsupporting
confidence: 92%
See 4 more Smart Citations
“…Based on the results of data analysis using SmartPLS, it obtained p value 0.000 < 0.050 so it can be concluded that Financial Literature had a significant effect on Students' Personal Financial Management, an increase in the Literature on Students variable would have a significant effect on an increase in the Students Personal Financial Management variable and a decrease in the Financial Literature variable would have an significant effect to the decrease in the Student Personal Financial Management variable. These results are in line with the research conducted by Chuah et al (2020), Cherney et al (2020), Humaidi et al (2020) that Financial Literature had a positive and significant effect on Students' Personal Financial Management. It concludes that personal management can be influenced simultaneously by variables of financial literacy, socioeconomic status, and lifestyle.…”
Section: Relationship Of Parents Social Economic On Students Personal Financial Managementsupporting
confidence: 92%
“…In Table 3 it can be explained that the adjusted R2 value of the independent variable his personal finances. According to Chuah et al (2020), Cherney et al (2020), Humaidi et al (2020) Lifestyle can be interpreted as the whole life of a person who relates to the environment and each other. The luxurious lifestyle is not only applied by teenagers whose economic level is upper middle class.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations